Enhanced molecular aging in late-life depression: the Senescent Associated Secretory Phenotype - Diniz, Breno Satler (Am J Geriatr Psychiatry, 2016)
OBJECTIVE: This study aims to investigate whether a systemic molecular pattern associated with aging (senescent-associated secretory phenotype – SASP) is elevated in adults with late-life depression (LLD), compared to never-depressed elderly comparison participants. DESIGN: Cross-sectional study. PARTICIPANTS: We included 111 older adults (80 with LLD and 31 comparison participants) in this study. MEASUREMENT: A panel of 22 SASP-related proteins was extracted from a previous multiplex protein panel performed in these participants. We conducted a principal component analysis to create the SASP index based on individual weights of each of protein. RESULTS: Participants with LLD showed a significantly increased SASP index compared to comparison participants, after controlling for age, depressive symptoms, medical comorbidity (CIRS-G) scores, gender, and cognitive performance (F((1,98))=7.3, p=0.008). Correlation analyses revealed that the SASP index was positively correlated with age (r=0.2, p = 0.03) and CIRS score (r=0.27, p=0.005), and negatively correlated with information processing speed (r=−0.34, p=0.001), executive function (r=−0.27, p=0.004) and global cognitive performance (r=−0.28, p=0.007). CONCLUSIONS: To the best of our knowledge, this is the first study to show that a set of proteins (i.e., SASP index) primarily associated with cellular aging, is abnormally regulated and elevated in LLD. These results suggest that individuals with LLD display enhanced aging-related molecular patterns that are associated with higher medical comorbidity and worse cognitive function. Finally, we provide a set of proteins that can serve as potential therapeutic targets and biomarkers to monitor the effects of therapeutic or preventative interventions in LLD.